Comparing the Effectiveness of Cognitive-Behavioral Therapy With an Integrated Package of Gestalt Therapy and Cognitive-behavioral Therapy on the Self-efficacy of Women With Breast Cancer - Mehrnoosh Makri Vala; Kiomars Farahbakhsh; Hossein Salimi Bajestani; Jalil Younesi Boroujeni (Iran University of Medical Sciences, 2022)
Background: Breast cancer, as the most common prevalent cancer in Iran, is associated with severe psychological consequences. This study aimed to compare the effectiveness of Cognitive-Behavioral Therapy (CBT) with an integrated package of Gestalt Therapy and Cognitive-Behavioral Therapy (GT-CBT) on the self-efficacy of women with breast cancer. Methods: This research was a quasi-experimental study with a pre-test, post-test design and a control group. Sixty patients with breast cancer referred to the Cancer Clinic of Imam Khomeini Hospital in Tehran City, Iran, were recruited through a convenience sampling method. They were randomly assigned to the control (n=20), CBT (n=20), and GT-CBT (n=20) groups. The study data were collected by the Sherer self-efficacy scale and analyzed using descriptive (Mean±SD) and inferential statistics (analysis of covariance [ANCOVA]) in SPSS software, v. 20. Results: The results indicated that both CBT and GT-CBT have significantly increased the subjects' self-efficacy (Eta=0.73, F51, 2=70.60, P<0.001). Post hoc test indicated that GT-CBT is more effective than CBT (P<0.05). Conclusion: The effectiveness of GT-CBT on the subjects' self-efficacy was higher than CBT. Therefore, it is suggested to use integrated methods such as GT-CBT to enhance the self-efficacy of patients with breast cancer.